2020
DOI: 10.1200/jco.2020.38.4_suppl.513
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib study of lenvatinib (LEN) plus nivolumab (NIV) in patients (pts) with unresectable hepatocellular carcinoma (uHCC): Study 117.

Abstract: 513 Background: LEN, a multikinase inhibitor of VEGFR 1–3, FGFR 1–4, PDGFRα, RET, and KIT with immunomodulatory activity, is approved in multiple countries for first-line treatment of uHCC. NIV is an anti-PD-1 monoclonal antibody approved in multiple countries as a second-line treatment for HCC. We report early results from a phase 1b trial of LEN + NIV in pts with uHCC. Methods: In this open-label study, pts with uHCC, BCLC stage B (not eligible for transarterial chemoembolization) or C, Child-Pugh class A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 0 publications
3
78
0
Order By: Relevance
“…In other words, because MTA are expected to have a certain effect irrespectively of any immune class of HCC, sequential therapy using MTA [44][45][46][47][48][49][50][51] is extremely important in the treatment of the WNT/β-catenin mutation. Most interestingly, the PD rates in combination trials of pembrolizumab plus lenvatinib [23], and nivolumab plus lenvatinib [41], were considerably lower (7 and 8.3%, respectively) than those of nivolumab (37%) [20] or pembrolizumab monotherapy (32.4%) [21]. The PD rate of 7-8.3% is lower than the rate of the immune exclusion class with WNT-β-catenin mutation of 20-30% [10,11].…”
Section: Potential Treatment Strategymentioning
confidence: 93%
See 1 more Smart Citation
“…In other words, because MTA are expected to have a certain effect irrespectively of any immune class of HCC, sequential therapy using MTA [44][45][46][47][48][49][50][51] is extremely important in the treatment of the WNT/β-catenin mutation. Most interestingly, the PD rates in combination trials of pembrolizumab plus lenvatinib [23], and nivolumab plus lenvatinib [41], were considerably lower (7 and 8.3%, respectively) than those of nivolumab (37%) [20] or pembrolizumab monotherapy (32.4%) [21]. The PD rate of 7-8.3% is lower than the rate of the immune exclusion class with WNT-β-catenin mutation of 20-30% [10,11].…”
Section: Potential Treatment Strategymentioning
confidence: 93%
“…5, 7). Furthermore, the ORR (RECIST version 1.1) for pembrolizumab plus lenvatinib (36%) [23] and nivolumab plus lenvatinib (54.2%) [41] is higher than that of the phase 3 atezolizumab plus bevacizumab combination (IMbrave150; 27.3%). This could be attributed to the higher antitumor effect of lenvatinib over bevacizumab [42][43][44][45], specifically, a more effective induction of necrosis in cancer cells, enhanced induction of DC induced by an increased neoantigen release, and more potent trafficking and infiltration of CD8 + T cells into tumors.…”
Section: Possible Treatment Strategy For the Immune Subclass Includinmentioning
confidence: 97%
“…At the ASCO-GI 2020 meeting, Kudo et al ( 63 ) reviewed the data of a phase IB trial that focused on the efficacy of nivolumab combined with lenvatinib in advanced HCC. The study enrolled 30 patients who were randomly divided into two groups: One group (n=6) had multidrug resistance and the other group (n=24) had no previous treatments.…”
Section: Application Of Pd-1/pd-l1 Inhibitors In Hccmentioning
confidence: 99%
“…If the effects of anti-PD-1/PD-L1 plus anti-VEGF antibodies reported in the phase III IMbrave150 study are confirmed in future clinical studies of early and intermediate stages of HCC, this therapy should greatly extend patient survival. ICI monotherapy regimens that inhibit only CheckMate 459 [5] KEYNOTE-240 [6] phase 1b (arm F) [19] phase 1b (arm F) [19] IMbrave150 [7] phase 1b (arm A) [19] phase 1b [17] phase 1b [18] ORR, % 13.6 (12.1-14.9)…”
Section: Resultsmentioning
confidence: 99%